PENGELOLAAN KAS (APBD) PADA BADAN PENGELOLAAN KEUANGAN DAN ASET DAERAH - Febri Yuliani, Sugesti, Meyzi Heriyanto, (Jurnal Ilmu Administrasi Negara, 2019)
Cash Management (APBD) at the Regional Financial and Asset Management Agency. This type of research is qualitative. This study aims to find out and analyze Cash (APBD) carried out by the Regional Asset Management and Asset Management Agency (BPKAD) of Rokan Hulu Regency as well as existing obstacles in cash management (APBD). The informants in this study were the head of the Regional Asset and Financial Management Agency of Rokan Hulu Regency, Secretary, Budget Head, Treasury Head and other informants related to the problems under study. Data obtained by conducting interviews, observation and documentation. The method used is descriptive with a qualitative approach by analyzing data through procedures for data reduction, data presentation and drawing conclusions. The results showed that overall cash management (APBD) in the Rokan Hulu District Government managed its regional finances including 5 indicators, namely Accountability, Value for money, Honesty in managing public finances (Probity), Transparency and Control were fairly good.